Outpatient orthognathic surgery: a prospective study of predictive factors for the length of hospital stays - Prevost, Alice; Lauwers, Frédéric; Varazzani, Andréa; Poulet, Vinciane; Mure, Marion; Lopez, Raphael; Cavallier, Zoé (Clinical oral investigations, 2023)
Objectives Transitioning from non-outpatient orthognathic surgery to outpatient surgery is a new challenge, and it is essential to target the eligible population as precisely as possible. Several authors describe series of outpatient orthognathic surgery but do not include the reasons for their success or failure. The main aim of this study was to identify the factors significantly associated with “successful” outpatient orthognathic treatment. The secondary objective was to determine the factors significantly associated with prolonged hospital stays (≥ 2 nights). Materials and methods A prospective cohort study including patients undergoing orthognathic surgery was conducted over a period of 1 year. We recorded the prognostic factors that contributed to successful outpatient treatment and prolonged hospital stays. These factors were evaluated by bivariate and multivariate analysis. Results A total of 102 patients were included, and the success rate of treatment was 65%. The variables that were isolated by multivariate analysis were: patients over the age of 22, procedures ending before 1 pm, brief operations, the absence of both postoperative vomiting and the administration of morphine. Conclusion Patient selection, organisation of outpatient facilities and anaesthetic protocols contribute to the development of outpatient orthognathic surgery. These initial considerations provide a framework for our practice, but the considerations that predict the failure of outpatient surgery will need to be clarified. Clinical relevance Orthognathic surgery can be performed on outpatient basis in selected cases. Age, the operative time, procedure end time, postoperative vomiting and the administration of morphine are associated with the success of outpatient care.